Kontrastivitas Onomatope Bahasa Jepang Dan Bahasa Sunda - Novitasari, Raden (KIRYOKU, 2025)
This research aims to examine and compare Japanese and Sundanese onomatopoeia. seen from the phonological elements, it is associated with form and meaning. The theories used to carry out data analysis are theories about phonology in Japanese and Sundanese as well as theories about onomatopoeia classification in Japanese and Sundanese. This research examines the comparison of Japanese and Sundanese onomatopoeia, so that the method used to analyze the data is a matching method with articulatory phonetic discrimination and translational discrimination. The research data is in the form of onomatopoeia based on sound imitations that are similar in Japanese and Sundanese. The research results obtained are Japanese and Sundanese onomatopoeia which have similar phonological forms, similar phonological forms in prefixes, insertions or endings, and onomatopoeia with dissimilar phonological forms.